The conditions of community customs transit (TAC) operations on the northern border of the ecuadorian state - Realpe Cabrera, Iván Alírio; Chunés Jácome, Jorge Luis; Herrera García, Eliana Aracely (SATHIRI, 2021)
In Ecuador, there is not enough development of research on logistics and transportation issues, and even more on community customs transit (TAC); the objetive of this research is to determine which are the conditions of community customs transit operations (TAC) in the northern border of Ecuador, focusing on providing guide to correct performance, pertinence, as well as legal gaps in the Andean community regulations. It is easy to find that, this regime presents unwanted events and failures, due in many cases to TAC particularities. Qualitative-quantitative research predominated in this research work, particular conditions of some variables that occur in the (TAC) operation were identified as well as some descriptions focused on the practice of customs regime by the cargo’s international transport companies working in the northern borderline. With the explanatory research, it was possible to verify whether the current conditions of operations carried performed in TAC affects an adequate regulatory and logistical application. From the surveys applied to 8 companies that carry out the TAC, and an objective population of 139, it was found that 75% taxes consolidation at foreign trade of this regime is carried out based on departing customs house; 50% apply the decision 837-2019 CAN, and finally, 37% express that there are cases which are not regulated at community level.